Coronary computed tomography angiography: an overview of clinical applications - Sun, Zhonghua; Almoudi, Mansour (Future Medicine Ltd, 2013)
High diagnostic accuracy has been achieved with coronary CT angiography using 64- and more slice CT scanners, and in selected patients, coronary CT angiography is considered a reliable alternative to invasive coronary angiography. Coronary CT angiography is able to detect variable densities in the coronary atherosclerotic plaques and demonstrate the corresponding intraluminal changes due to presence of plaques, thus providing prognostic value of disease extent. Despite the tremendous contributions of coronary CT angiography to cardiac imaging, coronary CT angiography suffered from high radiation dose, which has raised serious concerns in the literature. The aim of this review is to provide an overview of the clinical applications of coronary CT angiography in coronary artery disease with focus on diagnostic and predictive value of coronary CT angiography; technical developments of cardiac CT imaging and different approaches for radiation dose reduction.